Experimental and field record of preferred temperature in the neotropical amphisbaenid Amphisbaena mertensi stauch (reptilia, amphisbaenidae) - Abe, Augusto Shinya [UNESP] (Elsevier B.V., 1984)
1. 1. Temperature preference in experimental thermal gradient in the laboratory was determined and field preferred temperature was recorded, for Amphisbaena mertensi. 2. 2. Mean preferred temperature in 52 experiments averaged 21.4°C which was close to those recorded in 16 specimens measured in the field (21.1°C). 3. 3. Selected temperature varied from 12 to 27°C in the laboratory, and data taken in the field ranged from 18 to 26°C. © 1984.